Root growth, crop productivity, nutrient uptake and economics of dwarf pea (Pisum sativum) as influenced by integrated nutrient management - KUMARI, ANUPMA; SINGH, O N; KUMAR, RAKESH (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted during the two consecutive rabi seasons of 2007-08 and 2008-09 at Varanasi on sandy loam soil to study the effect of organic, inorganic and biofertilizers on dwarf pea (Pisum sativum L.). The experiment was conducted in a split-plot design and replicated thrice. All the fertility levels, viz. chemical fertilizers, vermicompost and control were allotted to main plot and combinations of biofertilizers (Rizobium+Bacillus polymixa +Pseudomonas fluorescence) and Zn along with control were subjected to sub-plot. Results showed superimposition of 50% Norganic (recommended dose of N through vermicompost) to 100% NPK (recommended dose of NPK through chemical fertilizers) resulted in significant improvement of dry matter/plant, yield (grain and straw, harvest index), root growth (root dry weight, root N content and cation exchange capacity of root) and nutrient uptake (NPKS and Zn). However nodulation (root nodules/plant, dry weight of nodules/plant and nitrogenase activity at 30 and 60 DAS) was lesser with this fertility level but significantly higher than 100% NPK and control (no application).Gross and net returns (` 45 358 and 31 223/ha) were noted higher with 100% NPK + 50% Norganic fertility level. Benefit: cost ratio (2.21) was also recorded higher with 100% NPK + 50% Norganic level. The integrated application of biofertilizers and Zn was recorded significantly better than control as this treatment lucidly improved dry matter, yield, harvest index, root growth, nodulation and nutrient uptake. Benefit: cost ratio was also higher with combined application of PSB and Zn. Furthermore, integration of 100% NPK + 50% Norganic and biofertilizers + Zn was conducive for getting significantly optimum yield (1873 kg/ha).